2021
DOI: 10.3390/geosciences11040171
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Stone Habitats in Coastal Waters of the Southwestern Baltic Sea (Hohwacht Bay)

Abstract: Cobbles and boulders on the seafloor are of high ecological value in their function as habitats for a variety of benthic species, contributing to biodiversity and productivity in marine environments. We investigate the origin, physical shape, and structure of habitat-forming cobbles and boulders and reflect on their dynamics in coastal environments of the southwestern Baltic Sea. Stone habitats are not limited to lag deposits and cannot be sufficiently described as static environments, as different dynamic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…However, the timescale in their study was of decades. The study area in this work has similar bed sediments and wave heights as in [48], but boulders could be more susceptible to sediment transport in the present study area due to the shallow water depth conditions in Rødsand lagoon. Yet, it is unlikely to find boulders exposed after 2015, though two boulders that were identified only on orthophotos after 2015 may have been unexposed prior to 2015.…”
Section: Evaluation Of Methods To Identify Boulders and Verified Boul...mentioning
confidence: 80%
See 1 more Smart Citation
“…However, the timescale in their study was of decades. The study area in this work has similar bed sediments and wave heights as in [48], but boulders could be more susceptible to sediment transport in the present study area due to the shallow water depth conditions in Rødsand lagoon. Yet, it is unlikely to find boulders exposed after 2015, though two boulders that were identified only on orthophotos after 2015 may have been unexposed prior to 2015.…”
Section: Evaluation Of Methods To Identify Boulders and Verified Boul...mentioning
confidence: 80%
“…Ref. [48] concluded that exposure of cobbles and boulders from glacial till by erosion is the main driver for stone habitat dynamics. However, the timescale in their study was of decades.…”
Section: Evaluation Of Methods To Identify Boulders and Verified Boul...mentioning
confidence: 99%
“…In this approach, we considered the whole sand fraction as part of the littoral sediment budget vs, which may lead to an overestimation of the budget volume by the varying amount of the fine-grained particles (0.063-0.2 mm).At the same time, there is the risk of an underestimation of the budget volume by the coarser sediment fraction: Besides the sandy sediments, larger stones and boulders are mobilized from the Pleistocene cliff deposits and contribute to the beach and nearshore sediment [11,24]. Due to issues of sample representativity and difficulties in the analyses of the coarse grain size fractions [67], the literature lacks quantitative data of those fractions.…”
Section: Sediment Fraction Nmentioning
confidence: 99%
“…For grain sizes >64 mm (cobbles, boulders), no quantitative data were available. Although stones and boulders have been proven to be partly mobile in the nearshore system [11,24], they are underrepresented in this study's budget estimation.…”
Section: Sediment Fraction Nmentioning
confidence: 99%
See 1 more Smart Citation